Dual diagnosis among veterans in the United States. Issue 1 (16th February 2015) - Crane, Cory A.; Schlauch, Robert C.; Easton, Caroline J.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Over the course of their service, veterans are exposed to elevated levels of chronic stress that contribute to a greater prevalence of mental illness than observed in the general population. When mental illness is present, comorbidity is normative. Convergent evidence suggests that co-occurring substance use and mental illness is among the most prevalent forms of comorbidity within veteran samples. The purpose of this paper is to explore issues associated with dual diagnoses among veterans in the USA. Design/methodology/approach – Research on dual diagnoses among veterans was reviewed and consolidated for presentation into three substantive content areas consisting of prevalence, associated conditions, and treatment of dual diagnoses. Findings – Dually diagnosed veterans represent a group at particularly high risk for myriad adverse biopsychosocial and treatment outcomes, including poor health, suicidality, violence or aggressive behavior, arrest, homelessness, and unemployment. A comprehensive strategy has been implemented within the Veterans Health Administration to address dual diagnosis and related problems. Additional research is required to more readily identify co-occurring substance use and mental illness and to refine integrated intervention approaches to minimize burden while improving treatment outcomes for veterans and their families. Originality/value – The current review includes a wide range of research spanning more than two decades and describing dual diagnosis among combat veterans of all modern eras. Areas in need of further research (e.g. dual diagnosis among female veterans; early detection of psychopathology and fully integrated care among returning veterans) are identified and discussed.